SEM study of resin tags depth for filled pit and fissure sealants using subpressure and adhesive system - An experimental analysis - Waghmode, Sonali; D, Shashikiran; Hadakar, Savita; Gaonkar, Namrata; Gugawad, Sachin (Asian Journal of Medical Sciences, 2023)
Background: Pit and fissure caries account for about 90% of the caries of permanent posterior teeth and 44% of caries within the first teeth in children and adolescents. Sealant application may be a preventive conservative approach. However, it is still challenging to bolster the retention of the filled sealant and to chop back the microleakage. Aims and Objectives: To evaluate and compare the depth of resin tags of three filled pit and fissure sealants (PFS) using subpressure and adhesive system under scanning electron microscope (SEM). Materials and Methods: This study was in vitro experimental study. Forty-five orthodontically extracted premolars were prepared for resin tag depth measurement and divided according to materials and subgroups. Group A- Resin-based filled PFS, Group B- Resin modified glass ionomer-based filled PFS, Group C- Giomer based filled PFS. Subgroup 1- Only sealant application, Subgroup 2- Subpressure application, Subgroup 3-Adhesive system + Subpressure application. Samples were subjected to thermocycling. The sectioned tooth fragments were polished using a carbide stone and then mounted under SEM for analysis. Photographs of the sections were obtained and the resin tag lengths were measured. Unpaired t-test and one-way analysis of variance test used for analysis. Results were considered significant when P<0.05. Results: The depth of resin tags of the tested materials differed significantly for Giomer-based and resin-modified glass ionomer-based filled PFS group with P<0.05. Whereas Resin-based filled PFS group was not found significant P>0.05 for the depth of resin tags. Conclusion: This study concludes that Giomer based filled PFS group and Resin-modified glass ionomer-based filled PFSs showed the highest Resin tag depth respectively when compared with Resin-based filled PFSs. The Subpressure application group was more effective followed by Adhesive+subpressure application group and Control group.